Analisa Hasil Uji Impak Sampah Plastik Jenis PP, PET, dan Campuran (PP + PET) - Wawan Trisnadi Putra; Ismono Ismono; Fadelan Fadelan; Yoyok Winardi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2017)
Material Plastic is difficult to decompose, so it needs to be held research on utilization of plastic waste that is around us. Impact test on recycled plastic waste aims to find out the physical properties, tenacity, toughness of plastic waste re-rubbish. Specimens of impact test based on standard sample (ASTM E-23) with Charpy test rod has dimension of size is 10 x 10 x 100 mm (height x width x length). With the notch position in the center, with a V note notch, 2 mm notch depth from the surface of the specimen and 45º notch angle. The specimens were made according to the sample with the test carried out 10 times, with the result of the average value of the specimens being the polypropylene type plastic of the mean energy impact value = 1.31 joule and the mean impact strength value = 0.0161 joule / mm². Polyethylene Terephthalate plastics with mean value of impact energy = 1.15 joule and mean impact strength = 0,0138 joule / mm², plastic mixture between PP and PET value of impact energy = 1.18 joule and mean impact strength = 0.0145 joule / mm². The results of this Polypropelin plastic test have the highest impact value value for recycled plastic waste.